Various jump training styles for improvement of vertical jump performance. - Waller, M.; Gersick, M.; Holman, D. (Strength and Conditioning Journal, 2013)
The improvement of an athlete's vertical jumping ability is a vital contribution to overall sports performance. Vertical jump performances occur in multiple situations from a static start, countermovement action, approach, and in response to landing. The methods by which power is assessed may influence the data collected, and thus, consideration should be made on the mode. The specifics of the various types of jumps will be discussed in the article, providing background information on the muscular actions, jump techniques, progression, and application for the improvement of vertical jump performance.